Invigoration of expired local rice seeds with organic priming treatment of noni fruit extract and soaking period - Antar Sofyan; Noorkomala Sari; Nor Annisa Helmasari (Universitas Trunojoyo Madura, 2026)
Rice is the primary staple food for most of the Indonesian population. Seed deterioration during storage reduces germination ability and threatens rice production. Seed invigoration through priming can restore seed quality by activating pre-germinative metabolism before radicle emergence. This study aimed to determine the best combination of organic priming using noni fruit extract and soaking period on the invigoration of expired local rice seeds. The research used a Completely Randomized Design (CRD) factorial experiment with a separate control was used, comprising 12 treatment combinations each repeated three times (39 experimental units). The first factor was the concentration of noni fruit extract (M) with four levels (0%, 1.5%, 3%, and 4.5%), and the second factor was the soaking period with three levels (12, 24, and 48 hours). Seeds were germinated using the UKDdp method with 50 seeds per roll. Organic priming with noni fruit extract combined with a soaking period significantly improved all measured germination parameters, including maximum growth potential, simultaneity of growth, germination capacity, vigor index, and growth speed of the deteriorated local rice seeds (variety Buyung Banjar). The best treatment combination was 4.5% noni fruit extract with a 24-hour soaking period (M3T2), which increased germination capacity by 1.6-fold and vigor index by 2.13-fold compared to the untreated control.